Rosyjskie jubileusze jako zjawiska retoryczno-ironiczne - Hordecki, Bartosz (Przegląd Politologiczny, 2018)
The objective of the paper is to present Russian anniversaries that commemorate important historical events as phenomena with a dual, rhetorical and ironic character. Rhetoric and irony are used with reference to individuals as well as imagined communities, such as nations. The memory of some historical events, or the lack of such memory, as well as the manners of referring to these events or ignoring them, result in the transformation of what community members think about themselves and their entanglement in common existence and fate. Therefore, changes of remembrance and oblivion, recollection or forgetting can integrate or disintegrate, intensifying the pride or shame of one’s national identity, which eventually results in satisfaction or frustration, and sometimes in a sense of superiority or inferiority. Pride and satisfaction are produced by rhetoric, while shame and frustration – by irony. Sometimes rhetorical-ironic playing with the past assumes particular significance, becoming an exceptionally important factor in social and political life. This phenomenon strongly intensified in Russia in the beginning of the 20th century, becoming a veritable ‘anniver- sary-mania’, and in 2012, which President of the Russian Federation, Dmitry Medvedev, de- clared the Year of Russian History. The periods analyzed in the paper are around one hundred years apart. Russian society has totally changed over this period, mainly as a result of the revolution, two world wars and several decades of communist rule. In 1990, the Russian Federation was established, a state with an authoritarian-democratic hybrid of a political system. Despite these transformations, modern Russians repeat numerous set behavioral patterns from the beginning of the 20th century. These patterns are used by the advocates of affirmative as well as critical approaches to the history of Russia and the current social and political situation in the country.